Effects of the automation on work content – selected issues - Jabłoński, Marek (Wpływ automatyzacji na treść pracy – wybrane aspekty, 2019)
Modern work processes are conditioned by many factors, among which technical progress seems to be a key determinant. In that respect, automation and its implementation within business processes as the result of technical progress, changes the content of the work of production and office processes, modifies job requirements for employees as well as the demand for many professions, and also generates completely new areas of human activity. The paper presents the social effects of automation from the perspective of changes in the content of work caused by the technical progress of work processes. As part of the defined intention, three phenomena describing the impact of technical progress on the content of the work were identified, i.e. no-skill-biased technical change, skill-biased technical change and talent-biased technical change. Referring to representative scientific research, the potential scope of automation was also presented. In particular, there was pointed out that activities most susceptible to automation include physical activities in highly structured and predictable environments, as well as data collection and processing
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 151-158
Keywords: automation; technical progress; content of work; automatyzacja; postęp techniczny; treść pracy